PILOT SURVEY OF PATIENT SATISFACTION TOWARDS OUTPATIENT SERVICES AT A TERTIARY CARDIAC CARE HOSPITAL - Pervaiz, Farrah; Zaidi, Sabeen Khurshid; Naqvi, Shahab; Siddiqa, Aysha; Khalil, Hafsa; Shah, Asmat Abbas (Pakistan Armed Forces Medical Journal, 2020)
Objective: To evaluate patient satisfaction in an outpatient department services of a tertiary cardiac care hospital.Study Design: Descriptive cross-sectional study.Place and Duration of study: Outpatient department of AFIC&NIHD Rawalpindi Pakistan from 1st November to 31st December, 2014.Methods: Patient representative sample was selected through purposive convenience sampling consisting of outpatients visiting a tertiary cardiac center. A structured pre-tested questionnaire was applied through interview, including the following variables: personal characteristics (gender, age, and occupation), distribution of responses toward various OPD services including physical facilities, doctor services and pharmacy services.Results: Maximum number of patients n = 533(53%) were in the age group of 41 to 60 years. Amongst them 847(84%) patients were males and 153(15%) were females. Majority of patients were retired army personnel 253(25%) and serving army personnel 209 (20%) whereas 360(36%) of the patients were reluctant to disclose their occupation. Overall satisfaction towards OPD services was 96%. The areas where satisfaction was lessthan 80% were pharmacy services.Conclusion: Evaluation allowed a better knowledge about the provided service and discretely delineated the key areas for continual improvement in quality of outpatient healthcare although a high level of satisfaction regarding the provided service was observed.